2004
DOI: 10.2337/diacare.27.6.1324
|View full text |Cite
|
Sign up to set email alerts
|

Ragaglitazar Improves Glycemic Control and Lipid Profile in Type 2 Diabetic Subjects

Abstract: OBJECTIVE -Ragaglitazar is a novel insulin sensitizer with dual peroxisome proliferatoractivated receptor (PPAR)-␥ and PPAR-␣ stimulating activities that improve plasma glucose and lipid profiles. The aim of the present dose-ranging study was to assess the efficacy and safety of ragaglitazar in patients with type 2 diabetes.RESEARCH DESIGN AND METHODS -This study included 177 hypertriglyceridemic type 2 diabetic subjects who participated in a 12-week, double-blind, parallel, randomized, placebo-controlled dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 23 publications
1
39
1
Order By: Relevance
“…In searching for a molecular link for the hematological system involvement, we note that the expression of PPAR ␥ in hematopoietic cells and its colocalization with the hematopoietic transcription factor PU.1 suggest a role in hematopoiesis ( 17,18 ). Interestingly, thiazolidinediones, which are artifi cial PPAR ␥ ligands, can cause nondilutional anemia ( 19 ) ( 20 ),cytopenias, and pancytopenia (21)(22)(23)(24). Although our study was not designed to study molecular or cellular mechanisms of the hematological abnormalities, we hypothesize that the multiple cytopenias might be caused either by abnormal bone marrow adipocytes, which are critical to support hematopoiesis ( 25,26 ), or an intrinsic hematopoietic defect causing a decreased survival or ineffi cient production.…”
Section: Assessment Of Dominant-negative Activity Of Mutant Ppargmentioning
confidence: 99%
“…In searching for a molecular link for the hematological system involvement, we note that the expression of PPAR ␥ in hematopoietic cells and its colocalization with the hematopoietic transcription factor PU.1 suggest a role in hematopoiesis ( 17,18 ). Interestingly, thiazolidinediones, which are artifi cial PPAR ␥ ligands, can cause nondilutional anemia ( 19 ) ( 20 ),cytopenias, and pancytopenia (21)(22)(23)(24). Although our study was not designed to study molecular or cellular mechanisms of the hematological abnormalities, we hypothesize that the multiple cytopenias might be caused either by abnormal bone marrow adipocytes, which are critical to support hematopoiesis ( 25,26 ), or an intrinsic hematopoietic defect causing a decreased survival or ineffi cient production.…”
Section: Assessment Of Dominant-negative Activity Of Mutant Ppargmentioning
confidence: 99%
“…All cases of systemic oedema (pretibial or facial) reported in a trial of troglitazone therapy occurred at about 2 months [23]. Patients withdrew early from a 12-week TZD study due to oedema, and effects on both white blood cell count and haemoglobin levels have been reported to occur with 4 weeks of treatment [24]. These investigators found that many of the actions of pioglitazone occur early and are maintained.…”
Section: Introductionmentioning
confidence: 97%
“…For example, both glycemic efficacy and edema formation are dose-dependent features of TZD therapy (10). Furthermore, peroxisome proliferator-activated receptor (PPAR)␥ agonists with more potent glucose-lowering effects seem to be associated with a higher incidence of edema formation (12). Besides a metabolic effect, insulin also has important vascular properties at several sites of the vascular tree.…”
mentioning
confidence: 99%